The unwanted : a novel - Fishman, Boris, 1979- (Harper, an imprint of HarperCollinsPublishers, 2025)
"Award-winning, New York Times Notable author of A Replacement Life-"a born storyteller with a tremendous gift for language" (San Francisco Chronicle)- delivers a fierce and staggering new page-turner full of cruelty, tenderness, and heroism, about a young girl and her parents fleeing civil war and the brutal dictatorship that has targeted their family. Susanna, George, and their eight-year-old daughter, Dina, have been lucky, so far, in these four years since war broke out in their country. Even as their fellow "minority-sect" neighbors and classmates are murdered or imprisoned, George's loyal work teaching "dominant-sect" literature has kept them fed and protected. But then the day comes: the university fires George-despite his years of collaboration, he is no longer safe. Left without money or allies, it is time for the family to run. Embarking on a harrowing trip through refugee camps and across the sea, both George and Susanna are forced in their own ways to make sacrifices to keep Dina safe, while Dina fights to understand the chaotic world crashing down around her. But with each member of the family struggling to survive in circumstances beyond their control, lies and betrayals multiply until it seems impossible for any of them to reach across the abyss. The Unwanted is a stunning story of what the most powerless among us will do for dignity and safety."--